DESAIN SILABUS MATRIKULASI BAHASA ARAB PMIAI ICAS-PARAMADINA JAKARTA - Mauidlotunnisa Mauidlotunnisa (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2014)
The aim of this research is to design a Arabic theaching syllabus for students at PMIAI ICASParamadina Jakarta that focused on Islamic philosophy and mysticism. The syllabus is an integrated syllabus which combines topics and academic reading skill based on Arabic for Academic Purposes. The process of syllabus design began with need analysis both internally and externally under the qualitative and quantitativ method. Based on the research findings, it is known that students in PMIAI ICAS-Paramadina Jakarta need an Arabic matriculation for reading and understanding texts since their Arabic proficiency level has not been adequate yet to conduct reading and understanding Islamic philosopy and mysticism texts in Arabic. DOI: 10.15408/a.v1i1.1132